It is the vendor that sells 1.5 L for $2.70
Answer: 1, 7, 1, 7, 1.
Step-by-step explanation:
The given function :
and f(1) = 1 for n ≥ 1
We put value of n=1,2,3,4 , we get
For n=1 , ![f(2)=f(1+1)=-2f(1)+8=-1(1)+8=-1+8=7](https://tex.z-dn.net/?f=f%282%29%3Df%281%2B1%29%3D-2f%281%29%2B8%3D-1%281%29%2B8%3D-1%2B8%3D7)
For n=2 , ![f(3)=f(2+1)=-2f(2)+8=-1(7)+8=1](https://tex.z-dn.net/?f=f%283%29%3Df%282%2B1%29%3D-2f%282%29%2B8%3D-1%287%29%2B8%3D1)
For n=3 , ![f(4)=f(3+1)=-2f(3)+8=-1(1)+8=7](https://tex.z-dn.net/?f=f%284%29%3Df%283%2B1%29%3D-2f%283%29%2B8%3D-1%281%29%2B8%3D7)
For n=4 , ![f(5)=f(4+1)=-2f(4)+8=-1(7)+8=1](https://tex.z-dn.net/?f=f%285%29%3Df%284%2B1%29%3D-2f%284%29%2B8%3D-1%287%29%2B8%3D1)
Hence, the first five terms of the given sequence are 1, 7, 1, 7, 1.
Answer:
1.) 48
2.) 65
3.) 36
Step-by-step explanation:
1.) If the equation is 6(x-4) and x = 12, then all we have to do is plug in the value of x. When we plug in, all we do is substitute 12 for x because they mentioned in the question that x = 12. So, we end up getting 6(12 - 4). After solving this, we get 48.
2.) This problem is a lot like the last problem. All we need to do is substitute /plug in the values of x and y into the equation, to get 4(4^2) - 35/7 - (8 + 14). After solving, we get 65.
3.) . This problem, once again, is also a lot like the last problems. We need to substitute the value of x into the equation 8x+12. Since we know from the problem that x is 3, all we have to do is 8 * 3 + 12.
Answer: x = 2
<u>Step-by-step explanation:</u>
![2^{2x}-2^x-12=0\\\\\text{Let u = }2^x\\\\u^2-u-12=0\\(u-4)(u+3)=0\\\\u-4=0\quad and\quad u+3=0\\u=4\qquad and\quad u=-3\\\\\text{Substitute u with }2^x\\2^x=4\qquad and \quad 2^x=-3\\2^x=2^2\quad and\quad \text{not possible}\\\boxed{x=2}](https://tex.z-dn.net/?f=2%5E%7B2x%7D-2%5Ex-12%3D0%5C%5C%5C%5C%5Ctext%7BLet%20u%20%3D%20%7D2%5Ex%5C%5C%5C%5Cu%5E2-u-12%3D0%5C%5C%28u-4%29%28u%2B3%29%3D0%5C%5C%5C%5Cu-4%3D0%5Cquad%20and%5Cquad%20u%2B3%3D0%5C%5Cu%3D4%5Cqquad%20and%5Cquad%20u%3D-3%5C%5C%5C%5C%5Ctext%7BSubstitute%20u%20with%20%7D2%5Ex%5C%5C2%5Ex%3D4%5Cqquad%20and%20%5Cquad%202%5Ex%3D-3%5C%5C2%5Ex%3D2%5E2%5Cquad%20and%5Cquad%20%5Ctext%7Bnot%20possible%7D%5C%5C%5Cboxed%7Bx%3D2%7D)
********************************************************************************
Answer: x = 0
<u>Step-by-step explanation:</u>
![3^{2x}+3^{x+1}-4=0\\\\3^{2x}+3^x\cdot3^1-4=0\\\\\text{Let u = }3^x\\u^2+3u-4=0\\\\(u+4)(u-1)=0\\\\u+4=0\quad and\quad u-1=0\\u=-4\qquad and\quad u=1\\\\\text{Substitute u with }3^x\\3^x=-4\qquad and\quad 3^x=1\\\text{not possible}\ and\quad 3^x=3^0\\.\qquad \qquad \qquad \qquad \boxed{x=0}](https://tex.z-dn.net/?f=3%5E%7B2x%7D%2B3%5E%7Bx%2B1%7D-4%3D0%5C%5C%5C%5C3%5E%7B2x%7D%2B3%5Ex%5Ccdot3%5E1-4%3D0%5C%5C%5C%5C%5Ctext%7BLet%20u%20%3D%20%7D3%5Ex%5C%5Cu%5E2%2B3u-4%3D0%5C%5C%5C%5C%28u%2B4%29%28u-1%29%3D0%5C%5C%5C%5Cu%2B4%3D0%5Cquad%20and%5Cquad%20u-1%3D0%5C%5Cu%3D-4%5Cqquad%20and%5Cquad%20u%3D1%5C%5C%5C%5C%5Ctext%7BSubstitute%20u%20with%20%7D3%5Ex%5C%5C3%5Ex%3D-4%5Cqquad%20and%5Cquad%203%5Ex%3D1%5C%5C%5Ctext%7Bnot%20possible%7D%5C%20and%5Cquad%203%5Ex%3D3%5E0%5C%5C.%5Cqquad%20%5Cqquad%20%5Cqquad%20%5Cqquad%20%5Cboxed%7Bx%3D0%7D)
********************************************************************************
Answer: No Solution
<u>Step-by-step explanation:</u>
![4^x+6\cdot 2^x+8=0\\\\2\cdot 2^x+6\cdot 2^x+8=0\\\\\text{Let u = }2^x\\2u+6u+8=0\\8u+8=0\\8u=-8\\u=-1\\\\\text{Substitute u with }2^x\\2^x=-1\\\text{not possible}](https://tex.z-dn.net/?f=4%5Ex%2B6%5Ccdot%202%5Ex%2B8%3D0%5C%5C%5C%5C2%5Ccdot%202%5Ex%2B6%5Ccdot%202%5Ex%2B8%3D0%5C%5C%5C%5C%5Ctext%7BLet%20u%20%3D%20%7D2%5Ex%5C%5C2u%2B6u%2B8%3D0%5C%5C8u%2B8%3D0%5C%5C8u%3D-8%5C%5Cu%3D-1%5C%5C%5C%5C%5Ctext%7BSubstitute%20u%20with%20%7D2%5Ex%5C%5C2%5Ex%3D-1%5C%5C%5Ctext%7Bnot%20possible%7D)
********************************************************************************
Answer: No Solution
<u>Step-by-step explanation:</u>
<u>
</u>
<u />
The origin in a graph.<span />